Paclitaxel-Loaded Macrophage Membrane Camouflaged Albumin Nanoparticles for Targeted Cancer Therapy - Cao X (Dove Medical Press, 2020)
Xi Cao,1,2 Tingfei Tan,1,2 Dongchun Zhu,1,2 Haixia Yu,1,2 Yaru Liu,1,2 Haiyun Zhou,1,2 Yong Jin,3,4 Quan Xia1,2 1Department of Pharmacy, The First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 2The Grade 3 Pharmaceutical Chemistry Laboratory of State Administration of Traditional Chinese Medicine, Hefei, People’s Republic of China; 3Key Laboratory of Anti-Inflammatory and Immune Medicines, Ministry of Education, School of Pharmacy, Anhui Medical University, Hefei, People’s Republic of China; 4The Key Laboratory of Major Autoimmune Diseases, Anhui Province, Anhui Institute of Innovative Drugs, School of Pharmacy, Anhui Medical University, Hefei, People’s Republic of ChinaCorrespondence: Quan Xia Tel +86 551 62922154Email xiaquan2010@163.comBackground: Melanoma is the most common symptom of aggressive skin cancer, and it has become a serious health concern worldwide in recent years. The metastasis rate of malignant melanoma remains high, and it is highly difficult to cure with the currently available treatment options. Effective yet safe therapeutic options are still lacking. Alternative treatment options are in great demand to improve the therapeutic outcome against advanced melanoma. This study aimed to develop albumin nanoparticles (ANPs) coated with macrophage plasma membranes (RANPs) loaded with paclitaxel (PTX) to achieve targeted therapy against malignant melanoma.Methods: Membrane derivations were achieved by using a combination of hypotonic lysis, mechanical membrane fragmentation, and differential centrifugation to empty the harvested cells of their intracellular contents. The collected membrane was then physically extruded through a 400 nm porous polycarbonate membrane to form macrophage cell membrane vesicles. Albumin nanoparticles were prepared through a well-studied nanoprecipitation process. At last, the two components were then coextruded through a 200 nm porous polycarbonate membrane.Results: Using paclitaxel as the model drug, PTX-loaded RANPs displayed significantly enhanced cytotoxicity and apoptosis rates compared to albumin nanoparticles without membrane coating in the murine melanoma cell line B16F10. RANPs also exhibited significantly higher internalization efficiency in B16F10 cells than albumin nanoparticles without a membrane coating. Next, a B16F10 tumor xenograft mouse model was established to explore the biodistribution profiles of RANPs, which showed prolonged blood circulation and selective accumulation at the tumor site. PTX-loaded RANPs also demonstrated greatly improved antitumor efficacy in B16F10 tumor-bearing mouse xenografts.Conclusion: Albumin-based nanoscale delivery systems coated with macrophage plasma membranes offer a highly promising approach to achieve tumor-targeted therapy following systemic administration.Keywords: macrophage membrane, albumin nanoparticles, melanoma, paclitaxel, tumor-targeted therapy